A low-rebound and high-impermeability liquid alkali-free quick-setting agent and its preparation method and application

By using the modified nano -fiber decentralized liquid and other doses in the liquid alkaline -free speed coagulation, forming a network -like structure, solving the problem of high rebound rates and poor anti -seepage in the environment of jet concrete in the tunnel rich environment, realized A significant reduction of the rebound rate and the effect of improving anti -penetration performance.

CN118955003BActive Publication Date: 2025-01-24SHIJIAZHUANG CHANGAN YUCAI BUILDING MATERIALS +1

Patent Information

Application Number
CN202411419777.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-24
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

The existing liquid alkali-free quick-coagulant is not ideal for use in tunnel water-rich environments. The sprayed concrete has a long settling time, a high rebound rate, and poor permeability, which affects the construction progress and durability.

Method used

The low -rebound high -anti -penetrating liquid -free alkaline -free condensate is used, and the nanocarbon aluminum calcium aluminum aluminum aluminum derived nano fiber dispersal is used in situ. The regulator forms a network -shaped structure to improve the resistance and durability of concrete.

Benefits of technology

Significantly reduce the rebound rate of jet concrete, improve the resistance and durability of anti -penetration, enhance the early intensity and later intensity reservation rate of concrete, and meet the high standards of construction requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a low-rebound and high-impermeability liquid alkali-free quick-setting agent and a preparation method and application thereof, comprising the following raw materials in mass percentage: 60% to 67% coagulant, 5% to 8% solubilizer, 2% to 4% impermeability waterproofing agent, 2% to 3% early strength agent, 1% to 2% pH regulator, 0.5% to 1.5% suspending agent, and the rest is water. The preparation method thereof comprises the following steps: under stirring, coagulant, solubilizer, early strength agent, pH regulator, and impermeability waterproofing agent are sequentially added to a mixed system of water and suspending agent to obtain a low-rebound and high-impermeability liquid alkali-free quick-setting agent. The present invention provides a low-rebound and high-impermeability liquid alkali-free quick-setting agent, which is alkali-free, fluorine-free, and chlorine-free, has a low dosage, high early strength, good stability, can significantly reduce the rebound rate of shotcrete, and improve the impermeability of shotcrete, and is particularly suitable for construction projects such as tunnels with water seepage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of quick-setting agents, and in particular relates to a low-rebound and high-impermeability liquid alkali-free quick-setting agent and a preparation method and application thereof. Background Art

[0002] As an essential admixture for shotcrete, accelerators can promote the rapid setting and hardening of cement concrete and are widely used in tunnel construction of railway and highway projects. Liquid alkali-free accelerators, in particular, have been widely used in recent years due to their low alkali content, low corrosiveness, and no effect on the later strength and durability of concrete. However, the commercially available liquid alkali-free accelerators currently have the disadvantages of high dosage, poor stability, low early strength, poor compatibility with cement, and high rebound rate.

[0003] In recent years, major projects such as the Sichuan-Tibet Railway have been subjected to great challenges in the construction of tunnels due to complex construction environments such as water seepage, over-excavation, and weak surrounding rocks. In particular, under the construction conditions of large amounts of water seepage on the tunnel working surface, the application effect of liquid alkali-free quick-setting agents is often not ideal, the setting time of shotcrete is long, the rebound rate is high, and it is even as high as 30% or more. The anti-permeability of shotcrete is poor, and the anti-permeability grade is not high. Water seepage diseases of shotcrete in the initial support of tunnels often occur, seriously affecting the construction progress and the durability of shotcrete. The anti-seepage and waterproofing of shotcrete have become problems that need to be solved urgently. The main measures in the existing technology are grouting to block water when excavating the water-gushing section or setting up water diversion pipes at the concentrated water flow, which have problems such as complex procedures and high costs.

[0004] Therefore, how to provide a low-rebound and high-impermeability alkali-free liquid quick-setting agent for shotcrete, which can greatly reduce the rebound rate of shotcrete in a water-rich tunnel environment while improving the mechanical properties and durability of shotcrete is a technical problem that technical personnel in this field urgently need to solve. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a low-resilience and high-impermeability liquid alkali-free quick-setting agent and a preparation method and application thereof.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A low-resilience and high-impermeability liquid alkali-free quick-setting agent, comprising the following raw materials in percentage by mass:

[0008] 60%~67% coagulant, 5%~8% solubilizer, 2%~4% anti-seepage and waterproofing agent, 2%~3% early strength agent, 1%~2% pH adjuster, 0.5%~1.5% suspending agent, and the rest is water.

[0009] Beneficial effects: The low-rebound and high-impermeability alkali-free liquid quick-setting agent provided by the present invention uses in-situ growth of nano-calcium aluminate to modify the surface of nanofibers to obtain a nano-modified fiber dispersion, which is used as an anti-seepage and waterproof component for the preparation of an alkali-free liquid quick-setting agent. The obtained alkali-free liquid quick-setting agent is used for spraying concrete, has anti-seepage and waterproof functions, can improve the durability of concrete, and significantly reduce the rebound rate of spraying concrete in water-rich areas of tunnels. The anti-seepage and waterproof agent synergistically forms a cross-linked network structure with the suspending agent, and the three together with the pH regulator effectively improve the stability of the quick-setting agent of the present invention, and the storage stability period can reach more than 3 months.

[0010] Preferably, the coagulant is one or any combination of aluminum triformate, aluminum nitrate, aluminum dihydrogen phosphate and amorphous aluminum hydroxide;

[0011] Beneficial effects: The coagulant provides a large amount of aluminum ions, which react quickly when added to concrete to generate a large amount of calcium sulfonate, promoting rapid coagulation of cement. Compared with traditional aluminum sulfate components, it does not contain sulfate, reducing the risk of sulfate erosion of shotcrete and has no adverse effect on the durability of concrete.

[0012] Preferably, the solubilizer is one or any combination of ethanolamine, diethanolamine, and N-methyldiethanolamine.

[0013] Beneficial effect: the solubilizing agent component is an organic alcohol amine, which has a strong complexing ability for aluminum ions, greatly promotes the full dissolution of aluminum ions in the liquid phase, increases the aluminum content of the liquid, and makes the accelerating setting agent of the present invention have a significant accelerating setting effect.

[0014] Preferably, the early strength agent is one or any combination of nano-SiO2, nano-calcium carbonate and nano-CSH.

[0015] Beneficial effects: The early strength agent uses nano-silicon dioxide and nano-calcium carbonate, which improves the density of concrete through the synergistic effect of micro-aggregate effect and crystal nucleus effect, thereby improving the mechanical properties and durability. Nano-CSH hydrated calcium silicate can reduce the nucleation barrier of cement hydration, provide nucleation growth points for cement hydration products, and accelerate the cement hydration process. Compared with traditional early strength agents, it can more effectively improve the ultra-early 6h~24h compressive strength of mortar and concrete mixed with accelerators, and at the same time, the later strength guarantee rate is high.

[0016] Preferably, the pH adjuster is one or any combination of formic acid, phosphoric acid and oxalic acid.

[0017] Beneficial effects: The pH regulator component inhibits the hydrolysis and precipitation of aluminum ions in the accelerator, and at the same time reduces the viscosity of the liquid accelerator, thereby avoiding excessive viscosity after a long storage time or in a low-temperature environment, which makes it difficult to use; the suspending agent component, through high-speed shear stirring, fully swells the structure, greatly improves the suspension efficiency of the supersaturated aluminum phase material in the accelerator, and under the synergistic effect of the above-mentioned pH regulator, avoids the crystallization phenomenon of some suspended aluminum phase materials at room temperature or low temperature, and greatly improves the stability.

[0018] Preferably, the suspending agent includes pseudo-boehmite and one or any combination of xanthan gum, carrageenan and hydroxyethyl cellulose.

[0019] Preferably, the anti-seepage waterproofing agent is a modified nanofiber dispersion, and the nanoparticle size is 150-200 nm, and the preparation method thereof comprises the following steps:

[0020] Under stirring conditions, dispersant, nanofiber, organic modifier and defoamer are added to water, pH is adjusted to 11.0-12.0, and stirring is continued for 1h-2h to obtain a base material;

[0021] The calcium salt aqueous solution, aluminum salt aqueous solution and carbonate aqueous solution are simultaneously added dropwise to the base material, and then stirred and aged for 6 to 12 hours to obtain a modified nanofiber dispersion.

[0022] Preferably, the dropping time is 6-12 hours and the temperature is 60-80°C.

[0023] Preferably, the calcium salt is one or any combination of calcium formate, calcium nitrate and calcium nitrite;

[0024] The aluminum salt is aluminum nitrate and / or sodium metaaluminate;

[0025] The carbonate is potassium carbonate and / or sodium carbonate;

[0026] The nanofiber is one or any combination of sepiolite nanofiber, nanocellulose fiber, and nanocarbon fiber;

[0027] The mass percentages of the dispersant, nanofiber and organic modifier in the base material are 25%-30%, 8%-12% and 5%-10% respectively.

[0028] The dispersant is a polycarboxylic acid high-performance water reducer (GK-3000 early strength type, Shijiazhuang Changan Yucai Building Materials Co., Ltd.);

[0029] The organic modifier is one or any combination of AMP-95 (2-amino-2-methyl-1-propanol) and THEED (tetrahydroxyethylethylenediamine);

[0030] The defoamer is a polyether defoamer.

[0031] Beneficial effects: The anti-seepage waterproofing agent is a modified nanofiber dispersion, which can improve the bonding strength between shotcrete and the construction work surface, block the seepage channel under the construction conditions of water seepage, reduce the rebound rate of shotcrete, and greatly improve the anti-seepage performance of shotcrete. The modified nanofiber dispersion provided by the present invention grows nano-carbon calcium aluminate particles on the surface of nanofibers in situ, modifies the surface of nanofibers, and solves the agglomeration problem of nanofibers. The modified nanofibers have good dispersibility. As one of the components of the accelerator, they form a more stable three-dimensional spatial network structure in the accelerator system, and improve the storage stability of the accelerator; when added to shotcrete, the introduced modified nanofibers are more evenly dispersed in the concrete, reducing the porosity of the concrete, blocking the water penetration channel, improving the density of the concrete structure, and further improving the anti-seepage performance of the concrete. On the other hand, the introduced nano-carbon calcium aluminate can play a nucleus effect, accelerate the hydration rate of cement minerals, and thus improve the early strength.

[0032] A method for preparing a low-resilience and high-impermeability liquid alkali-free quick-setting agent comprises the following steps:

[0033] Under stirring, a coagulant, a solubilizer, an early strength agent, a pH regulator and an anti-seepage waterproofing agent are sequentially added to a mixed system of water and a suspending agent to obtain a low-resilience and high-anti-seepage type liquid alkali-free quick-setting agent.

[0034] Preferably, the method specifically comprises the following steps:

[0035] Weigh the raw materials according to the ratio, add the suspending agent into the water, turn on the high-speed shear disperser, stir at a high speed of 2000-5000rpm for 20-30min, add the coagulant under stirring, and stir for 30-60min; add the solubilizer, stir for 30-60min to obtain a uniform turbid liquid without solid particles; continue to add the early strength agent, stir for 10-20min; add the pH adjuster, stir for 10-20min; under high-speed stirring, uniformly add the anti-seepage waterproofing agent, the addition time is 1-2h, and continue to stir for 30-60min after the addition is completed, so as to obtain a low-resilience and high-anti-seepage liquid alkali-free quick-setting agent.

[0036] The invention discloses an application of a low-rebound and high-impermeability liquid alkali-free quick-setting agent in tunnel construction.

[0037] Beneficial effects: The low-rebound and high-impermeability liquid alkali-free quick-setting agent provided by the present invention is alkali-free, fluorine-free and chlorine-free, has a low dosage, high early strength and good stability, can significantly reduce the rebound rate of shotcrete and improve the anti-seepage performance of shotcrete, and is particularly suitable for construction projects such as tunnels with water seepage.

[0038] Compared with the prior art, the present invention has the following advantages and technical effects:

[0039] The low-rebound and high-impermeability liquid alkali-free quick-setting agent of the present invention is fluorine-free, alkali-free and chlorine-free, has high early strength, especially super-early age 6h compressive strength ≥3.5MPa, 1d compressive strength ≥18MPa, no later strength loss, 90d compressive strength retention rate ≥110%, and various indicators meet the requirements of GB / T35159-2017 and Q / CR807-2020 standards, and has good stability, a stable period of more than 3 months, and a low rebound rate of shotcrete constructed in a water seepage environment, with a rebound rate of <5%. At the same time, the low-rebound and high-impermeability liquid alkali-free quick-setting agent of the present invention has good impermeability and a high sulfate erosion resistance coefficient. The anti-seepage grade of the shotcrete mixed with the quick-setting agent can reach P12, which is particularly suitable for tunnel construction projects where there is water seepage in the rock strata. DETAILED DESCRIPTION

[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0041] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the present invention is further described in detail below in conjunction with specific implementation methods.

[0042] The raw materials in the embodiments of the present invention are obtained through commercial sources;

[0043] Unless otherwise specified, normal temperature or room temperature in the embodiments of the present invention refers to 20±3°C.

[0044] Example 1

[0045] A low-resilience and high-impermeability liquid alkali-free quick-setting agent, comprising the following raw materials in mass fractions:

[0046] 60% coagulant (aluminum triformate), 5.5% solubilizer (diethanolamine and ethanolamine mixed in a mass ratio of 4:1), 2% anti-seepage waterproofing agent, 2% early strength agent (nano CSH (GK-3Z nano-microcrystalline material, produced by Shijiazhuang Changan Yucai Building Materials Co., Ltd.)), 1% pH adjuster (formic acid), 0.5% suspending agent (xanthan gum and pseudo-boehmite mixed in a mass ratio of 1:10), and the rest is water, the total amount is 100%.

[0047] Among them, the anti-seepage waterproofing agent is a modified nanofiber dispersion, and its preparation method is:

[0048] (1) Prepare a 60wt% calcium nitrate solution, a 15wt% sodium aluminate solution, and a 10wt% sodium carbonate aqueous solution. 2+ 、Al 3+ 、CO3 2- The molar ratio is 4:2:1;

[0049] (2) Water and polycarboxylic acid high-performance water-reducing agent were added into a reaction container, a high-speed shearing disperser was turned on, a stirring speed was set to 2000 rpm, nano-sepiolite fiber was slowly added, a defoamer (XP-1, Shijiazhuang Changan Yucai Building Materials Co., Ltd.) was added in sequence, and then AMP-95 was added to adjust the pH to 11.5, and stirring was continued for 1 h to 2 h to obtain a base material; wherein the mass percentage contents of polycarboxylic acid water-reducing agent, nano-sepiolite fiber, and AMP-95 in the base material were 30 wt%, 10 wt%, and 6 wt%, respectively;

[0050] (3) The three solutions prepared in step (1) are simultaneously added dropwise to the base material obtained in step (2), wherein the total mass ratio of the three solutions to the base material is 1:1, the addition time is 6 hours, and the reaction temperature is controlled at 65°C. After the addition is completed, the heating switch is turned off, and the stirring aging time is 12 hours to obtain a modified nanofiber dispersion, which is an anti-seepage waterproofing agent.

[0051] A method for preparing a low-resilience and high-impermeability liquid alkali-free quick-setting agent comprises the following steps:

[0052] Weigh the raw materials according to the ratio, add the suspending agent into the water, turn on the high-speed shear disperser, stir at a speed of 2500rpm for 30 minutes, add the coagulant under stirring, and stir for 60 minutes; add the solubilizer and stir for 60 minutes to obtain a uniform turbid liquid without solid particles; continue to add the early strength agent and stir for 20 minutes; add the pH adjuster and stir for 20 minutes; under high-speed stirring, uniformly add the anti-seepage waterproofing agent for 2 hours, and continue stirring for 60 minutes after the addition is completed to obtain a low-resilience and high-anti-seepage liquid alkali-free quick-setting agent.

[0053] Example 2

[0054] A low-resilience and high-impermeability liquid alkali-free quick-setting agent, comprising the following raw materials in mass fractions:

[0055] 63% coagulant (aluminum triformate and aluminum dihydrogen phosphate in a mass ratio of 1:1), 7% solubilizer (diethanolamine), 3% anti-seepage and waterproofing agent, 2.5% early strength agent (nano-SiO2), 1.2% pH adjuster (phosphoric acid), 0.8% suspending agent (carrageenan and pseudo-boehmite mixed in a mass ratio of 1:10), and the rest is water, the total amount is 100%.

[0056] Among them, the anti-seepage waterproofing agent is a modified nanofiber dispersion, and its preparation method is:

[0057] (1) Prepare 55wt% calcium nitrate solution, 10wt% sodium aluminate solution, and 10wt% sodium carbonate aqueous solution. 2+ 、Al 3+ 、CO3 2- The molar ratio is 4:2:1;

[0058] (2) Water and polycarboxylic acid high-performance water-reducing agent were added into a reaction container, a high-speed shearing disperser was turned on, a stirring speed was set to 3000 rpm, nanocellulose fibers were slowly added, a defoaming agent (XP-1, Shijiazhuang Changan Yucai Building Materials Co., Ltd.) was added in sequence, and then AMP-95 was added to adjust the pH to 11.5, and stirring was continued for 1.5 h to obtain a base material; wherein the mass percentage contents of the polycarboxylic acid water-reducing agent, nanocellulose fibers, and AMP-95 in the base material were 25 wt%, 8 wt%, and 8 wt%, respectively;

[0059] (3) The three solutions prepared in step (1) are simultaneously added dropwise to the base material obtained in step (2), wherein the total mass ratio of the three solutions to the base material is 3:2, the addition time is 8 hours, and the reaction temperature is controlled at 75°C. After the addition is completed, the heating switch is turned off, and the stirring aging time is 12 hours to obtain a modified nanofiber dispersion, which is an anti-seepage waterproofing agent.

[0060] A method for preparing a low-resilience and high-impermeability liquid alkali-free quick-setting agent is the same as that in Example 1.

[0061] Example 3

[0062] A low-resilience and high-impermeability liquid alkali-free quick-setting agent, comprising the following raw materials in mass fractions:

[0063] 65% accelerator (aluminum nitrate and aluminum dihydrogen phosphate in a mass ratio of 1:1), 8% solubilizer (N-methyldiethanolamine), 3.5% anti-seepage waterproofing agent, 3% early strength agent (nano CSH (GK-3Z nano-microcrystalline material, produced by Shijiazhuang Changan Yucai Building Materials Co., Ltd.)), 1.5% pH adjuster (phosphoric acid), 1% suspending agent (hydroxyethyl cellulose and pseudo-boehmite mixed in a mass ratio of 1:10), and the rest is water, and the total amount is 100%.

[0064] Among them, the anti-seepage waterproofing agent is a modified nanofiber dispersion, and its preparation method is:

[0065] (1) Prepare a 60wt% calcium nitrate solution, a 13wt% sodium aluminate solution, and an 8wt% sodium carbonate aqueous solution. 2+ 、Al 3+ 、CO3 2-The molar ratio is 5:2:1;

[0066] (2) Water and polycarboxylic acid high-performance water-reducing agent were added into a reaction container, and a high-speed shear disperser was turned on, the stirring speed was set to 2000 rpm, and nano-sepiolite fiber was slowly added, and a defoamer (XP-1, Shijiazhuang Changan Yucai Building Materials Co., Ltd.) was added in sequence, and then THEED was added to adjust the pH to 12.0, and the stirring was continued for 2 h to obtain a base material; wherein the mass percentage contents of the polycarboxylic acid water-reducing agent, nano-sepiolite fiber, and THEED in the base material were 30 wt%, 12 wt%, and 9.5 wt%, respectively;

[0067] (3) The three solutions prepared in step (1) are simultaneously added dropwise to the base material obtained in step (2), wherein the total mass ratio of the three solutions to the base material is 3:2, the addition time is 10 hours, and the reaction temperature is controlled at 75°C. After the addition is completed, the heating switch is turned off, and the stirring aging time is 10 hours to obtain a modified nanofiber dispersion, which is the anti-seepage waterproofing agent.

[0068] A method for preparing a low-resilience and high-impermeability liquid alkali-free quick-setting agent is the same as that in Example 1.

[0069] Example 4

[0070] A low-resilience and high-impermeability liquid alkali-free quick-setting agent, comprising the following raw materials in mass fractions:

[0071] 67% accelerator (aluminum nitrate and aluminum dihydrogen phosphate in a mass ratio of 1:1), 8% solubilizer (diethanolamine, N-methyldiethanolamine and ethanolamine mixed in a mass ratio of 5:2:1), 4% anti-seepage waterproofing agent, 3% early strength agent (nano-SiO2), 1.5% pH adjuster (oxalic acid), 1.5% suspending agent (hydroxyethyl cellulose and pseudo-boehmite mixed in a mass ratio of 1:8), and the rest is water. The total amount is 100%.

[0072] Among them, the anti-seepage waterproofing agent is a modified nanofiber dispersion, and its preparation method is:

[0073] (1) Prepare a 57wt% calcium nitrate solution, a 12wt% sodium aluminate solution, and a 7wt% sodium carbonate aqueous solution. 2+ 、Al 3+ 、CO3 2- The molar ratio is 5:2:1;

[0074] (2) Water and polycarboxylic acid high-performance water-reducing agent were added into a reaction container, a high-speed shear disperser was turned on, a stirring speed was set to 4000 rpm, nano-carbon fibers were slowly added, a defoaming agent (XP-1, Shijiazhuang Changan Yucai Building Materials Co., Ltd.) was added in sequence, and then AMP-95 was added to adjust the pH to 12.0, and stirring was continued for 1-2 hours to obtain a base material; wherein the mass percentage contents of the polycarboxylic acid water-reducing agent, nano-carbon fibers, and AMP-95 in the base material were 30wt%, 10wt%, and 7wt%, respectively;

[0075] (3) The three solutions prepared in step (1) are simultaneously added dropwise to the base material obtained in step (2), wherein the total mass ratio of the three solutions to the base material is 1:1, the addition time is 12 hours, and the reaction temperature is controlled at 80°C. After the addition is completed, the heating switch is turned off, and the stirring aging time is 12 hours to obtain a modified nanofiber dispersion, which is the anti-seepage waterproofing agent.

[0076] A method for preparing a low-resilience and high-impermeability liquid alkali-free quick-setting agent is the same as that in Example 1.

[0077] Comparative Example 1

[0078] The difference from Example 1 is that no early strength agent component is added.

[0079] Comparative Example 2

[0080] The difference from Example 1 is that the anti-seepage waterproofing agent component is not added to the quick-setting agent.

[0081] Comparative Example 3

[0082] The difference from Example 1 is that the anti-seepage waterproofing agent component in the quick-setting agent is a nanofiber dispersion that has not been modified by calcium carbonaluminate.

[0083] Comparative Example 4

[0084] The difference from Example 1 is that the anti-seepage waterproofing agent component in the quick-setting agent is a nano-carbon calcium aluminate dispersion that does not contain nanofibers.

[0085] Technical effect:

[0086] The low-resilience and high-impermeability liquid alkali-free accelerator provided by the present invention (hereinafter referred to as liquid alkali-free accelerator) is recommended to be added in a dosage of 6% to 8% of the total amount of cementitious materials in shotcrete. After testing, the alkali content, chloride ion content and fluoride ion content of the liquid alkali-free accelerator prepared in Examples 1 to 4 all meet the general requirements of Q / CR 807-2020 "Liquid alkali-free accelerator for tunnel shotcrete" for alkali-free accelerators (alkali content ≤ 1.0%, chloride ion content ≤ 0.05%, fluoride ion content ≤ 0.05%). The Q / CR 807-2020 standard has the performance requirements for the neat paste and mortar mixed with liquid alkali-free accelerator as shown in Table 1.

[0087] Table 1 Performance requirements of paste and mortar mixed with liquid alkali-free accelerating agent

[0088]

[0089] Test Example 1

[0090] According to the detection method specified in Q / CR 807-2020 "Liquid Alkali-free Accelerator for Tunnel Shotcrete", the accelerators prepared in Examples 1 to 4 were tested for setting time, compressive strength and other indicators. The test cement was the benchmark cement P.I42.5, and the accelerator dosage was 6%.

[0091] The test examples without accelerating coagulant were used as blank groups.

[0092] The test results are shown in Table 2.

[0093] Table 2 Performance of liquid alkali-free accelerating agent (benchmark cement)

[0094]

[0095] It can be seen from the data in Table 2 that the low-resilience and high-impermeability liquid alkali-free quick-setting agent of the present invention has excellent performance, and the various performance indicators of Examples 1 to 4 meet the requirements of Q / CR 807-2020 and GB / T 35159-2017 standards. The liquid alkali-free quick-setting agent provided by Examples 1 to 4 of the present invention has high ultra-early age strength of 6 to 24 hours, a 6-hour compressive strength of more than 3.5 MPa, a 1-day compressive strength of more than 18 MPa, and no shrinkage in the later period, and even improves, a 28-day compressive strength ratio of more than 100%, and a 90-day compressive strength retention rate of more than 110%. Compared with Example 1, the quick-setting agents of Comparative Examples 1 to 4 have worse setting time and strength performance indicators.

[0096] Test Example 2

[0097] According to the test method for the stability of accelerators in the Q / CR 807-2020 standard, the alkali-free liquid accelerators of each embodiment and comparative example are stored at room temperature for a certain period of time. If the volume of the supernatant (or bottom sediment) in 100 mL of liquid accelerator is ≤5 mL, it is considered that the stability during the storage period is qualified, otherwise the stability is unqualified.

[0098] Table 3 Stability of liquid alkali-free accelerator

[0099]

[0100] “√”: Stability qualified, “×”: Stability unqualified

[0101] As can be seen from Table 3, the low-resilience and high-impermeability liquid alkali-free quick-setting agent of the present invention has good stability and a shelf life of more than 6 months, and is suitable for engineering projects in various complex construction environments. The liquid alkali-free quick-setting agents of the comparative examples have poor stability, especially the quick-setting agents of comparative examples 2 to 4, whose shelf lives are all less than 2 months.

[0102] Test Example 3

[0103] According to the method mentioned in Appendix G of JGJ / T372-2016 "Technical Specifications for Application of Shotcrete", the rebound rate of shotcrete mixed with the low-rebound and high-impermeability liquid alkali-free quick-setting agent of the present invention was tested in a water-rich tunnel; according to JGJ / T372-2016 "Technical Specifications for Application of Shotcrete" and GB / T 50082-2019 "Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete", the anti-permeability performance (anti-permeability grade) of shotcrete mixed with the low-rebound and high-impermeability liquid alkali-free quick-setting agent of the present invention was tested, and the test results are shown in Table 4. The cement used in the test was Lafarge P.O42.5 cement, and the water reducer was GK-3000 (standard type) polycarboxylic acid high-performance water reducer produced by Shijiazhuang Changan Yucai Building Materials Co., Ltd.

[0104] Table 4 Performance of shotcrete mixed with low-rebound and high-impermeability liquid alkali-free accelerator

[0105]

[0106] As can be seen from Table 4, under the same sprayed concrete mix ratio, the low-rebound and high-impermeability liquid alkali-free quick-setting agent of the present invention is used, and the rebound rate of the sprayed concrete is low (<5%), and the application effect is good. At the same time, the sprayed concrete mixed with the low-rebound and high-impermeability liquid alkali-free quick-setting agent of the present invention has excellent impermeability performance, and the impermeability grade reaches P10 or above. The liquid quick-setting agent of Comparative Example 1 does not contain an early strength agent component, so the early strength development is slow. In a water seepage environment, the rebound rate of the sprayed concrete exceeds 8%; the liquid alkali-free quick-setting agent of Comparative Example 2 does not contain an impermeability and waterproof component, resulting in that even if the dosage is higher than that of Example 1, the rebound rate of the sprayed concrete is still much higher than that of Example 1, and the impermeability grade of the sprayed concrete is low, only P6, which does not meet the requirement that the impermeability grade of the sprayed concrete in the water-rich rock layer should not be lower than P8 as specified in JGJ / T372-2016 "Technical Specifications for the Application of Sprayed Concrete". The sprayed concrete mixed with the quick-setting agents of Comparative Examples 3 and 4 has a high rebound rate and a relatively low impermeability grade.

[0107] In summary, the low-rebound and high-impermeability liquid alkali-free quick-setting agent of the present invention has good comprehensive performance, 6h compressive strength of mortar ≥3.5MPa, 1d compressive strength>18MPa, 90d compressive strength retention rate>110%, and has the characteristics of high compressive strength of mortar at ultra-early age of 6h~24h, high later strength retention rate, and good stability. Various performance indicators far exceed the standards Q / CR 807-2020 "Liquid alkali-free quick-setting agent for tunnel sprayed concrete" and GB / T35159-2017 "Accelerator for sprayed concrete". At the same time, using the quick-setting agent of the present invention, the rebound rate of sprayed concrete is greatly reduced, and the impermeability performance is significantly improved. The liquid alkali-free quick-setting agent of the present invention has a simple preparation process, is fluorine-free, alkali-free, and chlorine-free, is green and environmentally friendly, and is very suitable for promotion and application. It is particularly suitable for complex construction environments such as seepage and weak surrounding rocks, as well as engineering projects that require rapid support.

[0108] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A low-resilience and high-impermeability liquid alkali-free quick-setting agent, characterized in that: The following raw materials are included in mass percentage: 60%~67% coagulant, 5%~8% solubilizer, 2%~4% anti-seepage and waterproofing agent, 2%~3% early strength agent, 1%~2% pH regulator, 0.5%~1.5% suspending agent, and the rest is water; The anti-seepage waterproofing agent is a modified nanofiber dispersion, and the nanoparticle size is 150-200nm. The preparation method thereof comprises the following steps: Under stirring conditions, dispersant, nanofiber, organic modifier and defoamer are added to water, pH is adjusted to 11.0-12.0, and stirring is continued for 1 h-2 h to obtain a base material; Adding a calcium salt aqueous solution, an aluminum salt aqueous solution, and a carbonate aqueous solution to the base material simultaneously, stirring and aging for 6 to 12 hours to obtain a modified nanofiber dispersion; The solubilizer is one or any combination of ethanolamine, diethanolamine, and N-methyldiethanolamine; The early strength agent is one or any combination of nano-SiO2, nano-calcium carbonate and nano-CSH.

2. A low-resilience and high-impermeability liquid alkali-free quick-setting agent according to claim 1, characterized in that: The coagulant is one or any combination of aluminum triformate, aluminum nitrate, aluminum dihydrogen phosphate and amorphous aluminum hydroxide.

3. A low-resilience and high-impermeability liquid alkali-free quick-setting agent according to claim 1, characterized in that: The pH regulator is one or any combination of formic acid, phosphoric acid and oxalic acid.

4. The low-resilience and high-impermeability liquid alkali-free quick-setting agent according to claim 1, characterized in that: The suspending agent includes pseudo-boehmite, and also includes one or any combination of xanthan gum, carrageenan, and hydroxyethyl cellulose.

5. The low-resilience and high-impermeability liquid alkali-free quick-setting agent according to claim 1, characterized in that: The calcium salt in the calcium salt aqueous solution is one or any combination of calcium formate, calcium nitrate and calcium nitrite; The aluminum salt in the aluminum salt aqueous solution is aluminum nitrate and / or sodium metaaluminate; The carbonate in the carbonate aqueous solution is potassium carbonate and / or sodium carbonate; The nanofiber is one or any combination of sepiolite nanofiber, nanocellulose fiber, and nanocarbon fiber; The mass percentages of the dispersant, nanofiber and organic modifier in the base material are 25%-30%, 8%-12% and 5%-10% respectively.

6. A method for preparing a low-resilience and high-impermeability liquid alkali-free quick-setting agent according to any one of claims 1 to 5, characterized in that: The following steps are involved: Under stirring, a coagulant, a solubilizer, an early strength agent, a pH regulator and an anti-seepage waterproofing agent are sequentially added into a mixed system of water and a suspending agent to obtain a low-resilience and high-anti-seepage type liquid alkali-free quick-setting agent.

7. Use of a low-resilience and high-impermeability liquid alkali-free quick-setting agent as claimed in any one of claims 1 to 5 in tunnel construction.

Citation Information

Patent Citations

  • Impermeable accelerator and preparation method thereof

    CN115784664A

Cited By

  • Low-carbon high-impermeability sprayed concrete

    CN121202491A